(:unas) unassigned - Souleles, Nicos (My University, 2020)
Invited advisor for the ‘TESEO - Ariadne's thread in the digital age project’ that aims to design new educational models and new training profiles and raise awareness about the tools offered by today’s digital revolution; it also aims to increase the so-called digital soft skills that are essential for both for elementary users of digital media and those involved in information and communication technologies as well as professionals in the new cultural industries.